EVALUATING THE HIP RANGE OF MOTION USING THE GONIOMETER, THE NINTENDO WIIMOTE AND VIDEO TRACKING METHODS - Mahshid Yazdifar; Mohammadreza Yazdifar (European Scientific Journal, ESJ, 2015)
The range of motion (ROM) of the hip joint is an important clinical parameter used in diagnosing femoroacetabular impingement (FAI). Early detection of FAI helps people avoid the development of osteoarthritis. The goniometer is the most common method employed to measure joint angles. However, it has several limitations with respect to allowing clinicians to analyse the ROM at the gate, and tracking the hip joint during walking or in maximum squat. Motion capture devices used for analyzing the patient’s gait and assessing the condition of joints and bones are accurate but require significant logistical and financial investment. The Nintendo Wiimote, used typically in games, has found its way to medical applications such as rehabilitation interventions and shows promise. This is the first study of its kind to evaluate the goniometer, a bespoke Wiimote system as well as a marker-based motion capture (MoCap) system to measure ROM. The aim of the article is to develop and assess a reliable, validated, easy to apply but scientifically sound method to measure ROM. This study used three methods to measure ROM. Namely, a high-spec marker-based MoCap system (Vicon), a markerless MoCap system (bespoke Wiimote system) and the conventional goniometer to examine the range of motion of 20 subject volunteers. This is the first of its kind to evaluate these three methods. The intraclass correlation coefficient (ICC) of the three methods is higher than 0.8 which shows that the reliability of all the methods is adequate. The validity of the marker-based MoCap system and the bespoke Wiimote is the same and furthermore, it is sufficiently robust to be used in clinical assessment. The marker-based MoCap system has slightly higher reliability and validity compared to the bespoke Wiimote system but the latter is easier to deploy, lower in cost, a more portable method and allows surgeons to have one free hand in order to avoid pelvic rotation and errors. The limitation of this study was the use of non FAI volunteers. It is concluded that the Wiimote can be used instead of the goniometer in clinical settings. The Wiimote is easy to use, portable, reliable and accurate.